'Omics' biomarkers associated with chronic low back pain: protocol of a retrospective longitudinal study. Issue 10 (19th October 2016) - Allegri, Massimo; De Gregori, Manuela; Minella, Cristina E; Klersy, Catherine; Wang, Wei; Sim, Moira; Gieger, Christian; Manz, Judith; Pemberton, Iain K; MacDougall, Jane; Williams, Frances MK; Van Zundert, Jan; et al.
Abstract : Introduction: Chronic low back pain (CLBP) produces considerable direct costs as well as indirect burdens for society, industry and health systems. CLBP is characterised by heterogeneity, inclusion of several pain syndromes, different underlying molecular pathologies and interaction with psychosocial factors that leads to a range of clinical manifestations. There is still much to understand in the underlying pathological processes and the non-psychosocial factors which account for differences in outcomes. Biomarkers that may be objectively used for diagnosis and personalised, targeted and cost-effective treatment are still lacking. Therefore, any data that may be obtained at the '-omics' level (glycomics, Activomics and genome-wide association studies—GWAS) may be helpful to use as dynamic biomarkers for elucidating CLBP pathogenesis and may ultimately provide prognostic information too. By means of a retrospective, observational, case-cohort, multicentre study, we aim to investigate new promising biomarkers potentially able to solve some of the issues related to CLBP. Methods and analysis: The study follows a two-phase, 1:2 case–control model. A total of 12 000 individuals (4000 cases and 8000 controls ) will be enrolled; clinical data will be registered, with particular attention to pain characteristics and outcomes of pain treatments. Blood samples will be collected to perform -omics studies. The primary objective is to recognise genetic variants associated with CLBP; secondary objectives are to study glycomics and Activomics profiles associated with CLBP. Ethics and dissemination: The study is part of the PainOMICS project funded by European Community in the Seventh Framework Programme. The study has been approved from competent ethical bodies and copies of approvals were provided to the European Commission before starting the study. Results of the study will be reviewed by the Scientific Board and Ethical Committee of the PainOMICS Consortium. The scientific results will be disseminated through peer-reviewed journals. Trial registration number: NCT02037789; Pre-results.